2021
DOI: 10.1001/jamanetworkopen.2021.11329
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Survival Outcomes Associated With First-Line Immunotherapy, Targeted Therapy, and Combination Therapy for Metastatic Clear Cell Renal Cell Carcinoma

Abstract: Key Points Question What is the comparative effectiveness of first-line targeted therapy, immunotherapy, and combination therapy in a real-world cohort of patients with metastatic clear cell renal cell carcinoma? Findings In this propensity-matched cohort study of 5872 patients treated in real-world clinical practice, first-line immunotherapy and combination therapy were associated with improved overall survival compared with first-line targeted therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Baseline clinical characteristics of interest were defined a priori based on established associations with favorable OS or objective imaging response; these characteristics included IMDC risk group, 11 presence of sarcomatoid histological characteristics, 12 receipt of CN, 13 and sites of metastasis. 14 , 15 , 16 , 17 Although age 18 , 19 and sex 20 have not been reported to interact with outcomes associated with contemporary therapies for mRCC, these variables were included in the analysis because they had not been examined as confounders in large routine-practice data sets. In the adjusted logistic regression analysis, only CN (odds ratio [OR], 1.59; 95% CI, 1.04-2.43; P = .03), deferred nephrectomy (OR, 3.04; 95% CI, 1.03-8.97; P = .04), lung metastases (OR, 1.49; 95% CI, 1.01-2.20; P = .04), and favorable vs poor IMDC risk group (OR, 1.93; 95% CI, 1.10-3.39; P = .02) were associated with objective imaging response in a statistically significant and clinically meaningful manner ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Baseline clinical characteristics of interest were defined a priori based on established associations with favorable OS or objective imaging response; these characteristics included IMDC risk group, 11 presence of sarcomatoid histological characteristics, 12 receipt of CN, 13 and sites of metastasis. 14 , 15 , 16 , 17 Although age 18 , 19 and sex 20 have not been reported to interact with outcomes associated with contemporary therapies for mRCC, these variables were included in the analysis because they had not been examined as confounders in large routine-practice data sets. In the adjusted logistic regression analysis, only CN (odds ratio [OR], 1.59; 95% CI, 1.04-2.43; P = .03), deferred nephrectomy (OR, 3.04; 95% CI, 1.03-8.97; P = .04), lung metastases (OR, 1.49; 95% CI, 1.01-2.20; P = .04), and favorable vs poor IMDC risk group (OR, 1.93; 95% CI, 1.10-3.39; P = .02) were associated with objective imaging response in a statistically significant and clinically meaningful manner ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among these count multi‐target tyrosine kinase inhibitors (sunitinib, sorafenib and bevacizumab), mammalian target of rapamycin (mTOR) targeted drugs (temsirolimus and everolimus) and immune checkpoint inhibitors (avelumab, nivolumab and ipilimumab) (Mihaly et al, 2012). Especially treatments regimens combining targeted therapies and immune checkpoint inhibitors significantly improved overall survival in metastatic RCC (Chakiryan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Especially treatments regimens combining targeted therapies and immune checkpoint inhibitors significantly improved overall survival in metastatic RCC (Chakiryan et al, 2021).…”
mentioning
confidence: 99%
“…Systemic therapy against mRCC has evolved significantly over the past two decades [11][12][13][14]. Vascular endothelial growth factor (VEGF)-tyrosine kinase inhibitors (TKIs) (e.g., sunitinib, pazopanib, axitinib, tivozanib, lenvatinib, and cabozantinib) or mammalian target of rapamycin (mTOR) pathway inhibitors (e.g., everolimus and temsirolimus) were used in the 2000s for mRCC, either combined or as a monotherapy [11][12][13][14]. A validation study of the International Metastatic RCC Database Consortium (IMDC) system revealed that the median overall survival (OS) significantly improved in the 2000s as compared to that observed in the cytokine era (favorable risk: 43.2 months, intermediate risk: 22.5 months, and poor risk: 7.8 months) [15].…”
Section: Introductionmentioning
confidence: 99%
“…A validation study of the International Metastatic RCC Database Consortium (IMDC) system revealed that the median overall survival (OS) significantly improved in the 2000s as compared to that observed in the cytokine era (favorable risk: 43.2 months, intermediate risk: 22.5 months, and poor risk: 7.8 months) [15]. Unfortunately, the 5-year OS rate for mRCC remains under 30% despite the TKI-based approach [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%